Tradisi Badantam dalam Alek Perkawinan (Kajian Fungsionalisme Struktural) - Wita Harmaini; Khairil Anwar; Pramono Pramono (Jurnal Elektronik WACANA ETNIK, 2018)
This article contains a brief description of the badantam tradition that lives in the Kampung Kandang village in Pariaman. Badantam tradition is part of a tradition that lives in the community, which is in the traditional wedding ceremony. Badantam tradition aims to raise funds from the community donations of someone who married his child.Through this description, obtained the meaning contained in this tradition badantam. The meaning of badantam tradition includes self-esteem, social control, and cooperation.